2021
DOI: 10.1021/acsomega.1c05160
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Room-Temperature Thermoelectric Performance of n-Type Bi2Te2.7Se0.3

Abstract: Bi 2 Te 3 -based compounds are exclusive commercial thermoelectric materials around room temperature. For n-type compounds, optimal thermoelectric properties are normally obtained at temperatures higher than room temperature to suppress the bipolar effect through increased carrier concentration. We find that doping with trace amounts of Cd and the addition of excess Bi are effective ways to optimize carrier concentration and achieve enhanced room-temperature thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
2
7
1
Order By: Relevance
“…38,49 Under a similar assumption, the SPB model has also been applied to analyze several complex (including modulated) alloys. 18,38,49,50 It is worth noting that the carrier concentration in Bi 1−x Sb x alloy in the present case does not change much in going from x = 0.13 to 0.26, and the calculated n H values are comparable. This indicated that the carrier concentration for intermediate values of x (0.13 ≤ x ≤ 0.26) in the Bi 1−x Sb x alloy remained practically independent of the Sb content.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…38,49 Under a similar assumption, the SPB model has also been applied to analyze several complex (including modulated) alloys. 18,38,49,50 It is worth noting that the carrier concentration in Bi 1−x Sb x alloy in the present case does not change much in going from x = 0.13 to 0.26, and the calculated n H values are comparable. This indicated that the carrier concentration for intermediate values of x (0.13 ≤ x ≤ 0.26) in the Bi 1−x Sb x alloy remained practically independent of the Sb content.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…Assuming the single parabolic band (SPB) conduction model, we calculated the Hall carrier concentration n H (shown in Figures S4a) using n H = 1/ eR H , where e is the electronic charge. The single parabolic band (SPB) conduction model seems to be a good approximation for the analysis of modulated samples prepared in this study, which is based on the assumption that acoustic phonon and alloying scattering dominate carrier transport. , Under a similar assumption, the SPB model has also been applied to analyze several complex (including modulated) alloys. ,,, It is worth noting that the carrier concentration in Bi 1– x Sb x alloy in the present case does not change much in going from x = 0.13 to 0.26, and the calculated n H values are comparable. This indicated that the carrier concentration for intermediate values of x (0.13 ≤ x ≤ 0.26) in the Bi 1– x Sb x alloy remained practically independent of the Sb content.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…S6 (ESI) †. Clearly, the obtained large ZT values of the present BTS-based composites incorporating Ag 9 AlSe 6 inclusions are larger than most of the reported ZT values in typical n-type BTS-based composite systems 21,23,30,34–38 (see Fig. 5).…”
Section: Resultsmentioning
confidence: 56%
“…An enhancement of the ZT ave value can be found for the samples of BTS-0. larger than most of the reported ZT values in typical n-type BTS-based composite systems 21,23,30,[34][35][36][37][38] (see Fig. 5).…”
Section: Thermoelectric Propertiesmentioning
confidence: 58%